2022
DOI: 10.17503/agrivita.v44i1.3039
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis of Finger Millet Genotypes Across Diverse Hilly and Mountainous Environments in Nepal

Abstract: Journal of Agricultural Sciencewww.agrivita.ub.ac.id 199 Agriculture Development, 2018). The yearly stout crop is mostly cultivated in the tropical and subtropical parts of the world. Nepal has an abundant number of varieties of finger millet residing up to 3150 m.a.s.l. There are about 790 fingermillet accessions that are assembled from different parts of Nepal (Gairhe, Gauchan, & Timsina, 2021)production, productivity, and trade for the year 2009-2019. The study used a combination of exploratory survey and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…Madhavilatha et al (2020) reported average stability for grain yield was found in VR 990 which revealed the wide adaptability of the genotype across different locations Kandel et al (2022). studied genotypes viz., GE-0382, KLE-216, NE-94 and KLE-559 that were found environmentally sensitive producing higher grain yield throughout the environments.Patel et al (…”
mentioning
confidence: 98%
“…Madhavilatha et al (2020) reported average stability for grain yield was found in VR 990 which revealed the wide adaptability of the genotype across different locations Kandel et al (2022). studied genotypes viz., GE-0382, KLE-216, NE-94 and KLE-559 that were found environmentally sensitive producing higher grain yield throughout the environments.Patel et al (…”
mentioning
confidence: 98%